Microbiological quality on food handlers’ hands at primary schools in Hulu Langat District, Malaysia - Tan, S. L.; Lee, Hai Yen; Abu Bakar, Fatimah; Abdul Karim, Muhammad Shahrim; Rukayadi, Yaya; Mahyudin, Nor Ainy (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
A total of 85 food handlers participated in this study to determine the hygienic status of their hands in primary schools located in the state of Selangor (Malaysia). Overall findings revealed that the fecal contamination and personal hygiene of the food handlers were well maintained with the range of mean bacterial counts from 0.18 to 0.47 log 10 Colony Forming Units/cm 2 during the three intervals of hand swabbing (before, during and after) preparation of ready-to-eat foods. However, the general indication of the microbiological quality (Aerobic Plate Count) was out of the standard (range of mean bacterial counts from 1.39 to 1.56 log 10 Colony Forming Units/cm 2) based on previous literature. This study highlighted that the food handler’s adherence to Good Manufacturing Practice and Sanitation Standard Operating Procedures was insufficient and suggested that attention should be emphasized on their practices at the intervals of school recess: before, during and after the preparation of ready-to-eat foods. In addition, there is also a need in the implementation of an effective HACCP program in Malaysia school foodservice operations.